Turn-off fluorescence probe for the selective determination of pendimethalin using a mechanistic docking model of novel oxacalix[4]arene. Issue 58 (2nd June 2016) - Panchal, Manthan; Athar, Mohd.; Jha, P. C.; Kongor, Anita; Mehta, Viren; Bhatt, Keyur; Jain, Vinod
Abstract : A novel bidansylated oxacalix[4]arene (BDO) fluoroionophore for the selective determination of pendimethalin (PM) was carried out in the linear range of detection between 0.4 μM and 20 μM. Abstract : A novel bidansylated oxacalix[4]arene (BDO) fluoroionophore for the selective determination of pendimethalin (PM) was carried out in the linear range of detection between 0.4 μM and 20 μM. Furthermore, computational studies were performed to assess the binding and stability of the complex. For the predicted model, PM faces laterally and interacts via weak intermolecular forces with BDO with a E value of −176.00 kJ mol −1 .